Marine fisheries insurance in India: retrospect and prospects in the context of climate change - A Suresh; Vijay Kiran (Agricultural Economics Research Review, 2023)
Fishers often face risks to their life and fishing assets. Sudden changes in weather in the form of cyclones, tsunamis, collision of fishing vessels, and accidental firings constitute major perils that affect fishers. The weather fluctuations lead to an unstable income flow. Marine fishing insurance may help fishers protect themselves against climate risks. The insurance in fisheries sector has several learning lessons from the crop insurance schemes. This paper reviews the status of marine fisheries insurance in India and prospects for reforming it in the light of the experiences of the crop insurance schemes. The study uses both primary and secondary data. The primary data were collected using a snowball sampling technique from 200 fishermen in Kerala; 100 each from traditional fishers and trawl fishers. The data was supplemented by a case study of the Njarakkal-Nayarambalam Fishermen Welfare Cooperative Development Society in Ernakulam, Kerala which facilitates insurance coverage to traditional fishers. Also, three focused group discussions with the fishermen were carried out. The leaning lessons for fisheries insurance from the crop insurance in Kerala were derived following a literature review. All the traditional vessels (100%) in the sample were insured due to the operation of Matyafed, a cooperative venture supported by the Government of Kerala, which provides credit to the traditional fishermen where the insurance is bundled with credit. Vessels insurance has only marginal coverage with trawl fishers. The main reasons for the low subscription are high premiums, inadequate coverage of the loss, and previous experience of delays in settlement of indemnities. Lack of suitable insurance products and difficulty in verifiability affects also affects its deepening. Further, fishers perceive insurance as an additional expenditure, and are of the opinion that the community would take care of the loss to a certain extent. The weather index-based insurance as in the case of crops is an alternative solution.